Irrealism in ethics - Streumer, Bart (Chichester, West Sussex : Wiley Blackwell, 2014)
Irrealism in Ethics presents a collection of six original essays contributed by prominent moral philosophers that address various forms of the philosophical position of ethical irrealism. Addresses various forms of the philosophical position of ethical irrealismPresents arguments both for and against the two major versions of ethical irrealism-the error theory and expressivismOffers innovative new arguments on topics relating to ethical irrealismFeatures original contributions from internationally prominent moral philosophers.
Irrealism and the genealogy of morals / Richard Joyce -- A distinction without a difference? Good advice for moral error theorists / Hallvard Lillehammer -- Ethics without errors / James Lenman -- Faultless moral disagreement / Alison Hills -- Revolutionary expressivism / Sebastian Kohler and Michael Ridge -- Do normative judgements aim to represent the world? / Bart Streumer.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: 1900-1999; Ethics, Modern -- 20th century; Reality; Knowledge, Theory of; Normativity (Ethics); Philosophy; Reason; PHILOSOPHY -- Ethics & Moral Philosophy; PHILOSOPHY -- Social; Ethics, Modern; Reality; Electronic books; Electronic books